Withdrawal of antihypertensive medication: a systematic review - van der Wardt, Veronika; Harrison, Jennifer K.; Welsh, Tomas J.; Conroy, Simon; Gladman, John R.F. (Lippincott, Williams & Wilkins, 2017)
Although antihypertensive medication is usually continued indefinitely, observations during wash-out phases in hypertension trials have shown that withdrawal of antihypertensive medication might be well tolerated to do in a considerable proportion of people. A systematic review was completed to determine the proportion of people remaining normotensive for 6 months or longer after cessation of antihypertensive therapy and to investigate the safety of withdrawal. The mean proportion adjusted for sample size of people remaining below each study's threshold for hypertension treatment was 0.38 at 6 months [95% confidence interval (CI) 0.37–0.49; 912 participants], 0.40 at 1 year (95% CI 0.40–0.40; 2640 participants) and 0.26 at 2 years or longer (95% CI 0.26–0.27; 1262 participants). Monotherapy, lower blood pressure before withdrawal and body weight were reported as predictors for successful withdrawal. Adverse events were more common in those who withdrew but were minor and included headache, joint pain, palpitations, oedema and a general feeling of being unwell. Prescribers should consider offering patients with well controlled hypertension a trial of withdrawal of antihypertensive treatment with subsequent regular blood pressure monitoring.